PENGEMBANGAN MODEL ASESMEN BERBASIS KARAKTER UNTUK MENINGKATKAN NILAI-NILAI RELIGIUS PADA SISWA - Safitriana, Dian Ika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Character education is essential in shaping students to be not only intellectually capable but also morally and spiritually mature. In Indonesia, religious values are a central component of national education, as outlined in Law No. 20 of 2003, which emphasizes nurturing students to be believers, devoted to God, and of noble character. The Merdeka Curriculum reinforces this by placing "faith, devotion to God, and noble character" as the first dimension in the Pancasila Student Profile. However, in practice, the integration of religious values in elementary education remains largely normative and lacks structured learning and assessment approaches. Teachers often struggle with evaluating students"™ religious character development due to the absence of systematic and comprehensive assessment tools. Existing assessments tend to be subjective, inconsistent, and based on superficial observations without clear indicators. Additionally, religious character development activities in schools often take ceremonial forms"”such as communal prayers or holiday celebrations"”without truly instilling spiritual values into students"™ daily behavior. Given the challenges posed by globalization, moral decline, and cultural influences that conflict with national values, strengthening students"™ religious foundation is increasingly important. This research seeks to address these issues by developing and validating a character-based assessment model aimed at effectively measuring and nurturing religious values among elementary school students. The proposed model aspires to provide a more contextual, practical, and holistic approach to religious character education in schools.